Methotrexate and mucositis: A merry-go-round for oncologists - Mishra, Kundan; Jandial, Aditya; Kumar, Anil; Lad, Deepesh; Prakash, Gaurav; Khadwal, Alka; Malhotra, Pankaj (Indian Journal of Medical and Paediatric Oncology, 2019)
High-dose methotrexate is the backbone of various regimens for treating lymphoid malignancies. Mucositis is a well-known, dose-related side effect of methotrexate. Prophylactic measures such as folinic acid rescue are useful but do not prevent mucositis in all the cases. Once severe mucositis (WHO Grade IV) sets in, mortality is very high. The index case highlights the natural course of methotrexate-induced mucositis and the need for swift and preemptive intervention.
Keywords: Lymphoid malignancy; methotrexate; mucositis